High‐Efficiency (16.93%) Pseudo‐Planar Heterojunction Organic Solar Cells Enabled by Binary Additives Strategy. (16th June 2021) - Wang, Xinkang; Zhang, Lifu; Hu, Lei; Xie, Zijun; Mao, Houdong; Tan, Licheng; Zhang, Youdi; Chen, Yiwang
Abstract: Acquiring precision adjustable morphology of the blend films to improve the efficiency of charge separation and collection is a constant goal of organic solar cells (OSCs). Here, the above problem is improved by synergistically combining the sequential deposition (SD) method and the additive general strategy. By adding one additive 1, 10‐decanediol (DDO) into PM6 and another 1‐chloronaphthalene (CN) into Y6, the molecule orientation of PM6 and the crystallite texture of the Y6 all become order. During the SD processing, a vertical phase separation OSCs device is formed where the donor enrichment at the anode and acceptor enrichment at the cathode. In comparison, the SD OSCs device with only CN additive still displays the bulk‐heterojunction morphology similar to PM6:Y6 blend film. The morphology with vertical phase distribution can not only inhibit charge recombination but also facilitate charge collection, finally enhancing the fill factor (FF) and photocurrent in binary additives SD‐type OSCs. As a result, the binary additives SD‐type OSCs with blend film PM6+ DDO/Y6+ CN exhibit a high FF of 77.45%, enabling a power conversion efficiency as high as 16.93%. This work reveals a simple but effective approach for boosting high‐efficiency OSCs with ideal morphologies and demonstrates that the additive is a promising processing alternative. Abstract : 1, 10‐decanediol is introduced as an additive that can improve the crystalline of polymer and protect PM6 film from less erosion during the sequential deposition (SD) process. The strategy is applied to fabricate pseudo‐planar heterojunction (PPHJ) organic solar cells with ideal vertical phase separation through SD processing. The champion PPHJ device demonstrates a high efficiency (16.93%) and fill factor (77.45%).